How does water deficit induce changes in primary and secondary metabolism in Corymbia citriodora seedlings? - de Medeiros, Robson Luis Silva [UNESP]; Borjas-Ventura, Ricardo Roberto; de Souza, João Vitor Oliveira [UNESP]; Fernandes, João Pedro Peixoto [UNESP]; Gratão, Priscila Lupino [UNESP]; de Paula, Rinaldo Cesar [UNESP] (Instituto de Pesquisa e Estudos Florestais (IPEF), 2023)
Corymbia citriodora is a species of commercial importance planted by small - and medium-sized producers. It produces good quality wood and has been attracting the attention of the forestry market. The occurrence of abiotic stresses will be more and more frequent, caused by climate change, which can limit plant development. Water deficit is the main factor in the reduction of eucalyptus productivity. This research aimed to evaluate the effects of water stress on the development of C. citriodora plants. The seedlings were grown in pots and submitted to five irrigation regimes (20, 35, 50, 65, and 80% of the maximum soil water retention capacity) for 110 days in a greenhouse. Plant growth, gas exchange, leaf water potential, chlorophyll, carotenoid, proline, and lipid peroxidation by malondialdehyde (MDA) content were evaluated at the end of this period. The decrease in water availability may have provided a reduction in cell number, increasing the concentration of pigments, proline, and MDA, and a reduction in leaf water potential, gas exchange, and plant growth. C. citriodora seedlings showed a significant reduction in growth when grown at levels below 50% of the maximum soil water retention capacity.
Como a deficiência hídrica induz alterações no metabolismo primário e secundário em mudas de Corymbia citriodora?
Keywords: Drought sensitivity; Eucalyptus; Gas exchange; Oxidative stress; Seedling development